Influence of gender and academic level on the development of digital competencies in university teachers: a multidisciplinary comparative analysis - Moreira-Choez, Jenniffer Sobeida; Lamus de Rodríguez, Tibisay Milene; Arias-Iturralde, María Cristina; Vega-Intriago, Jisson Oswaldo; Mendoza-Fernández, Verónica Monserrate; Zambrano-Acosta, Jimmy Manuel; Cardenas-Hinojosa, Ruben Dario (Frontiers in Education, 2024)
Introduction In the digital era, the evolving demands of professional fields, especially in higher education, have accentuated the need for advanced digital competencies among faculty members. Digital competencies are now considered essential for effective teaching, necessitating an in-depth understanding of how these skills are distributed across different demographics, including gender and academic level. This study aims to explore the digital competencies of faculty members at the State University of Milagro, focusing on how these competencies vary by gender and academic level. Methods This study employed a quantitative approach within the positivist paradigm to assess the digital competencies of 279 faculty members at the State University of Milagro. Data were collected using the Higher Education Digital Competence Assessment Questionnaire, a validated instrument designed to measure various dimensions of digital skills. Descriptive statistical analysis was conducted using SPSS to evaluate the internal consistency of the competencies and to identify correlations among them, as well as to assess the influence of gender and academic level on these competencies. Results The analysis revealed significant correlations among the different dimensions of digital competencies, indicating that proficiency in one area often contributes to the development of skills in other areas. The integrative nature of digital technologies within the academic environment was evident, with a high level of internal consistency observed across the competencies assessed. Notably, differences were found based on gender and academic level, suggesting that these demographic factors influence technological exposure and training, with certain groups displaying higher competency levels in specific areas. Discussion The findings highlight the importance of promoting integrative educational strategies that consider the diverse backgrounds of faculty members to ensure equitable development of digital competencies. The observed gender and academic level disparities underline the need for targeted interventions that address the specific needs of different faculty groups. By fostering a more balanced development of digital skills, institutions can enhance overall teaching effectiveness and better prepare faculty to meet the demands of modern educational environments. These results contribute to the ongoing discourse on digital competency development in higher education and suggest avenues for further research on how to bridge existing gaps in digital skills among faculty.